The Effect of Customer Orientation and Product Innovation on Fashion Business Performance With Competitive Advantage as a Mediator - Mahendra, Agil Yusuf; Nuvriasari, Audita (CV. Rayyan Dwi Bharata, 2025)
This research aims to analyze the influence of customer orientation and product innovation on fashion business performance with competitive advantage as a mediator. The sample in this research was 50 respondents who were determined using a purposive sampling technique. The data collection method uses a questionnaire that is distributed directly. The analytical tools used in hypothesis testing are Outer Model analysis, Inner Model analysis and hypothesis testing with the t test. The results of this research prove that: (1) Customer Orientation has a positive and significant effect on Business Performance. (2) Product Innovation has a positive and significant effect on Business Performance. (3) Competitive Advantage has a positive and significant effect on Business Performance. (4) Customer Orientation has a positive and significant effect on Competitive Advantage. (5) Product Innovation has a positive and significant effect on Competitive Advantage. (6) The role of Competitive Advantage is able to mediate the influence of Customer Orientation on Business Performance. (7) The role of Competitive Advantage is able to mediate the impact of Product Innovation on Business Performance.